Finance for integrated landscape management. The potential of credit unions in Indonesia to catalyze local rural development. The case of Semandang Jaya Credit Union - Mawesti, D.; Aryanto, T.; Yogi, Y.; Louman, B. (Tropenbos International, 2021)
This case study focuses on the various types of productive loans provided by the Social Performance Management Unit of the Credit Union Semandang Jaya that are available to finance small-scale farmers and businesses, and analyzes how these are perceived to contribute to landscape objectives and integrated landscape management initiatives in the Ketapang-Kayong Utara landscape in West Kalimantan, Indonesia.